Fever-Induced Brugada-Pattern Electrocardiogram - Nugraha, Yudha Tria; Prasetya, Indra; Martini, Heny; Rizal, Ardian (Universitas Brawijaya, 2024)
Background: The Brugada syndrome is a type of cardiac arrhythmia frequently overlooked because of the dynamic character of the condition. Because it tends to progress into ventricular arrhythmias, it is a disorder that, if left untreated, carries the risk of being deadly. Not only is it essential for the practicing clinician to understand the situations that can disclose the concealed Brugada syndrome, but it is also essential for patients to understand these circumstances so that they can be educated to seek medical assistance quickly. This study aimed to describe the diagnosis and management of fever-induced Brugada pattern electrocardiogramCase presentation: Male in his 42-year-old with a history of intermittent fever for four days before hospital admission. High-degree fever was only relieved by taking antipyretics and was accompanied by nausea and muscle and joint pain. Upon arrival at the emergency department, he denied any complaints of chest pain or discomfort, shortness of breath, orthopnea, PND, leg swelling, palpitation, or syncope. A chest radiograph showed normal cardiac and pulmo (Figure 1); a first electrocardiogram showed Sinus Rhythm, HR 112 bpm, regular, FA normal, HA normal, P wave normal, PR interval 160 msec, QRS 80 msec, QTc 326 msec, Coved ST elevation at lead V1 (1 mm), V2 (3 mm), T inversion at lead V1-V2, suggesting sinus tachycardia with type II Brugada pattern.Conclusion: A Brugada pattern can be exposed to several stimuli, but fever is particularly potent. To assist urgent or emergency follow-up in cardiology, Emergency physicians must be informed of specific ECG findings based on the patient's clinical risk factors. The emergency doctor must be able to tell the difference between this pattern and a typical variation of RBBB, as a delayed diagnosis can have dire consequences.